Formula approach: strategies for improving vocational college students’ Malay essay writing skills - Nurul Aini Mohd Yunus,; Anies Faziehan Zakaria, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The acquisition of essay writing skills holds compulsory significance for all Malaysian Vocational Certificate (SVM) students at Vocational Colleges (KV), as these skills are embedded within the SVM Malay language course curriculum. Generally, students at KV exhibit a range of weak to moderate mastery levels in essay writing, particularly in terms of structuring and organizing essays in a systematic manner. Evidently, lackluster student performance was accentuated when a subset of students failed to respond adequately to essay prompts during the End of Semester Assessment, emerging as a substantial contributor to the failure rates within the Malay language subject. A survey unveiled a deficiency in systematic essay writing proficiency, resulting in student hesitancy and disinterest in addressing essay-related queries. In response, the researcher introduced a formulaic approach to essay writing with the aim of elevating student performance. A sample of 24 students from the Electronics Technology Program was selected randomly to participate in this study. Consequently, a study was conducted employing pre-test and post-test assessments to evaluate the effectiveness of the introduced formulaic approach within the study sample. The gathered data revealed a notable shift in student achievement levels, evidenced by improvements in grades post-intervention and alignment with the prescribed scoring criteria. Initially absent in pre-test outcomes, the attainment of an ‘A’ grade by the study sample became evident following the post-test, wherein the formulaic approach was integrated into the teaching and learning process. This study establishes that students are capable of proficiently and systematically honing their Malay essay writing skills. Through the implementation of a structured methodology, it becomes apparent that learners can effectively bridge identified gaps, thereby enhancing their overall mastery of the subject matter. Consequently, this research holds implications for pedagogical practices geared towards fostering heightened competency in essay writing among SVM students.